Analisis Harga Pokok Produksi dengan Metode Full Costing dalam Menetapkan Harga Jual - Eko Purwanto; Winda Irawati (LPPM UNIBI, 2020)
Cost of production is a collection of the costs incurred to process raw materials into finished goods. Calculation of the true cost of production, will result in the determination of the selling price is right anyway, So it will be able to generate profits as expected. CirengGonjreng is a Micro, Small, and Medium Enterprises that are still in the research period and in the registration process which is engaged in the production of typical food, Bandung, namely cireng. The study states that the calculation of the cost of production is generating significant differences that affect the determination of the selling price. To that end, the company should separate the costs of production and non-production costs and further optimize its production activities so as to produce the exact cost of production at a low cost, order that the company can earn a maximum profit.